The role of a pedagogical staff for providing the quality of higher education - Bebko, Svitlana (My University, 2020)
The article analyzes the notion of quality of higher education and the role of the teaching staff in the education processes. There have been featured the key trends that influence the activity of the departments of higher education institutions and increase their importance for providing quality of higher education. The theoretical foundations of the department functioning in the higher education system of Ukraine are generalized. In the process of research the author can conclude that: innovative changes occurring in higher education need to address the important issues of ensuring the quality of higher education; the effectiveness of the quality of higher education depends largely on the teaching staff of the departments; during the years of Ukraine's independence, both the negative and the positive phenomena occurred in the teaching staff of the department; it is important to improve the system of remuneration of teachers of higher education institutions, their social security, and to improve the conditions of their professional activity in accordance with European standards; efficiency of use of modern information technologies requires considerable financial and modern logistical support from the state. У статті проаналізовано поняття якості вищої освіти та роль професорсько-викладацького складу в навчально-науковому процесі. Охарактеризовані ключові тенденції, що впливають на діяльність кафедр вищих навчальних закладів, які підвищують їх значення в забезпеченні якості вищої освіти. Узагальнено теоретичні засади функціонування кафедри в системі вищої освіти України. Сформульовано висновки: інноваційні зміни, які відбуваються в сфері вищої освіти, потребують вирішення важливих питань забезпечення високої якості вищої освіти; ефективність якості вищої освіти в значній мірі залежить від професорсько-викладацького складу кафедр; за роки незалежності України в роботі професорсько-викладацького складу кафедри відбулися як негативні, так і позитивні явища; важливо вдосконалити систему оплати праці викладачів вищих навчальних закладів, їх соціальне забезпечення, поліпшення умов їх професійної діяльності відповідно до європейських стандартів; ефективність використання сучасних інформаційних технологій вимагає значної фінансової підтримки з боку держави, сучасного матеріально-технічного забезпечення.
Keywords: вищі навчальні заклади; педагогічний колектив; вища освіта; якість; ключові тренди; key trends; pedagogical staff; higher education; quality; higher education institutions; кафедра економіки і права